A Motherâ€™s Knowledge: The Value of Narrating Dis/Ability in Education - Connor, David J.; Berman, Diane Linder (European Scientific Journal, ESJ, 2016)
In this paper we answer the question: In what ways does a motherâ€™s narrative of including her son with a disability in his local school inform inclusive practices in general? Our research contains a theoretical framework informed by (1) Disability Studies in Education (DSE), (2) the importance of narrative knowing within research, and (3) the value of a motherâ€™s knowledge of her child. The data consists of the second authorâ€™s written autobiographical accounts of her experiences with, and observations of, her childâ€™s school. We feature a series of four vignettes culled from second authorâ€™s descriptions as a mother of a child who did not â€œfit the moldâ€ in terms of academic, social, and emotional expectations. Using analysis informed by DSE, coupled with personal reflection, the first author discusses the value of ways in which a motherâ€™s knowledge about human diversity and desire for inclusion counters the deficit-based assumptions and expectations entrenched in much of special educationâ€™s foundational thinking that, in turn, informs daily practices within schools that reinforces the exclusion of children with disabilities. Next, we link our findings to implications for the interrelated fields of education, special education, and inclusive education. Finally, we articulate some recommendations, based upon our work.